Possible superconductivity at ∼70 K in tin hydride SnHx under high pressure. (January 2022) - Hong, F.; Shan, P.F.; Yang, L.X.; Yue, B.B.; Yang, P.T.; Liu, Z.Y.; Sun, J.P.; Dai, J.H.; Yu, H.; Yin, Y.Y.; Yu, X.H.; Cheng, J.G.; et al.
Abstract: Hydrides of air non-sensitive IVA-group elements were predicted to be possible high temperature superconductors (HTS) by N.W. Ashcroft (PRL 92, 187002 (2004)), which inspired the exploration of hydrogen dominated metallic alloy-based HTS. Although the IVA-group hydrides have been investigated theoretically by several groups, the experimental realization of any superconducting IVA-group hydrides is still lacking. Here, we report on the observation of the possible superconducting transition at ∼70 K in a SnHx sample synthesized by laser heating Sn and ammonia borane inside a diamond anvil cell at ∼200 GPa. The main phase of the obtained sample can be indexed with the monoclinic C 2/ m SnH12 via comparison with the theoretical structural modes, which have distinct H-network with respect to the clathrate-type structure. A sudden drop of resistance and the systematic downward shift under external magnetic fields signal the occurrence of superconductivity in SnHx with an upper critical field μ 0 H c2 (0) ≈ 11.2 T, and the resistive broadening behavior in magnetic fields follows the trend of traditional standard superconductors. This work provides an alternative way to obtain metal hydrides HTS via p electron-metals rather than the active s or f electron-metals (such as Mg, Ca, La, Y, Ce), which will stimulate the experimental exploration of hydrides HTS in different element groups. Graphical abstract: A new metal hydride SnHx superconductor with T c ≈ 72 K is synthesized at ∼200 GPa. Image 1 Highlights: A new hydride SnHx is synthesized at ∼200 GPa, and is confirmed to be a high-temperature superconductor (HTS) with T c ≈ 72 K. The obtained SnHx is a p-electron metal hydride superconductor containing H2 and H4 molecule-like units. SnHx is the first experimentally synthesized HTS among the IVA-group hydrides.